Observational validation of Juan Enrique Azcoaga's pedagogical learning theory with CD1 mice - Aponte-Zumba, Jennifer Andrea; Martínez-Suárez, Pedro Carlos; Reiván-Ortiz, Geovanny Genaro; Ramírez-Coronel, Andrés Alexis (Revista Científica de la Facultad de Ciencias Veterinarias, 2022)
Juan Enrique Azcoaga defines learning as a process that affects human and animal behavior. The main objective of the present study is to describe and pre-experimentally validate Azcoaga's pedagogical learning theory through experimentation in mice of non-inbred lines CD1 strain. The pre-experimental laboratory method was used, at an explanatory-predictive level and with a qualitative approach; the procedure was carried out through the resolution of tasks of motivation, tonic-sustained attention and short and long term memory considered within the basic learning devices (DBA), for this purpose two biomodels (female and male) of the CD1 strain were randomly used for each task. The results obtained show that this theory is applicable to animal behavior, so there is similarity in the use of basic learning devices (DBA) in both humans and CD1 mice during the learning process. These findings suggest that this species were capable of identifying, recognizing and differentiating one task from another and achieving the purpose of each one of them, in addition to the fact that its memory allows it to evoke memories that structure its learning, thus confirming the hypothesis proposed.